2018
DOI: 10.1016/s2468-2667(18)30079-3
|View full text |Cite
|
Sign up to set email alerts
|

Midlife contributors to socioeconomic differences in frailty during later life: a prospective cohort study

Abstract: SummaryBackgroundHealth inequalities persist into old age. We aimed to investigate risk factors for socioeconomic differences in frailty that could potentially be modified through policy measures.MethodsIn this multi-wave longitudinal cohort study (Whitehall II study), we assessed participants' socioeconomic status, behavioural and biomedical risk factors, and disease status at age 45–55 years, and frailty (defined according to the Fried phenotype) at baseline and at one or more of three clinic visits about 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Additional research is needed to further specify and test the mechanisms underlying food insecurity [44] and provide an empirical base for the hypothesized relationships in Fig 1 [6,7,13,35,36,43,44]. Such research would inform a growing literature on the cumulative effects of hardships across the life course [62,65,66] and their role in accelerating aging [8,64,[67][68][69][70][71]. Further exploration of midlife vulnerability is needed to identify prevention and screening (e.g., primary care) strategies designed to halt or slow disease progression, promote rehabilitation, and increase wellness into later life [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to further specify and test the mechanisms underlying food insecurity [44] and provide an empirical base for the hypothesized relationships in Fig 1 [6,7,13,35,36,43,44]. Such research would inform a growing literature on the cumulative effects of hardships across the life course [62,65,66] and their role in accelerating aging [8,64,[67][68][69][70][71]. Further exploration of midlife vulnerability is needed to identify prevention and screening (e.g., primary care) strategies designed to halt or slow disease progression, promote rehabilitation, and increase wellness into later life [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that socioeconomic circumstances (educational level, income, employment status, etc. ), especially in late midlife, are strongly associated with living arrangements, social support, and health later in life (Brunner et al 2018). Educational level represents the most important proxy for the income capability and sociocultural resources of different individuals and, as such, is important to their chances of partnering and family formation (Bellani, Esping-Andersen, and Nedoluzhko 2017;Demey et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic variables that signi cantly differed between the group of older persons with GPC contact and the group of persons with no GPC contact were used as adjustment factors (confounders) in the multilevel analysis for outcome measures. Furthermore, we adjusted for SES in our frailty analyses, because frailty is associated with socioeconomic inequalities (27,28). Finally, we adjusted for hospital admission in the analysis of frailty in older persons, as this appeared to be a signi cant relevant factor.…”
Section: Discussionmentioning
confidence: 99%